Methods of Planning Per Yearly Training Stages in Wrestling Athletes (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
In recent years, special attention has been paid to the revival of the national sport of Kurash, the historical heritage of the Uzbek people, which has been revered for centuries as a symbol of courage, tolerance, nobility and honesty. Improving the system of training students in wrestling requires the search for new methodological approaches to the organization and content of the educational process, the choice of special training tools in accordance with the traditions of competition development.